The SAGE handbook of international higher education - Deardorff, Darla K.; Wit, Hans de, 1950-; Heyl, John; Adams, Tony (SAGE, 2012)
Contributors examine the internationalization of higher education years from a marginal to a core dimension of higher education worldwide. The Handbook presents an overview of developments, in a combination of issues and regional accounts.